2007
DOI: 10.1021/nl070013b
|View full text |Cite
|
Sign up to set email alerts
|

Polarizability of G4-DNA Observed by Electrostatic Force Microscopy Measurements

Abstract: G4-DNA, a quadruple helical motif of stacked guanine tetrads, is stiffer and more resistant to surface forces than double-stranded DNA (dsDNA), yet it enables self-assembly. Therefore, it is more likely to enable charge transport upon deposition on hard supports. We report clear evidence of polarizability of long G4-DNA molecules measured by electrostatic force microscopy, while coadsorbed dsDNA molecules on mica are electrically silent. This is another sign that G4-DNA is potentially better than dsDNA as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
92
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 26 publications
5
92
0
2
Order By: Relevance
“…Such rigidity is particularly appealing for the realization of conducting molecular bridges. Previously, we reported the synthesis [6,10] and EFM measurements [4] of intra-molecular G4-DNA (Figure 1b, left) which was stabilized by K⁺ cations. This type of intra-molecular G4-DNA possessed distinct polarizability, in contrast to native dsDNA, which gave no discernible signal.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Such rigidity is particularly appealing for the realization of conducting molecular bridges. Previously, we reported the synthesis [6,10] and EFM measurements [4] of intra-molecular G4-DNA (Figure 1b, left) which was stabilized by K⁺ cations. This type of intra-molecular G4-DNA possessed distinct polarizability, in contrast to native dsDNA, which gave no discernible signal.…”
mentioning
confidence: 76%
“…the tetrad unit and the tetrad-tetrad stacking. By comparing adjacent molecules of both types, co-adsorbed on the same mica surface, we circumvent the problem of phase calibration, showing that the EFM signal is twice as strong in the parallel configuration as compared with the anti-parallel G4-DNA, possibly because of greater charge mobility in tetra-molecular G4-DNA, thus making tetra-molecular G4-DNA a better candidate for conductivity measurements.Theoretical [7,8] and experimental [4,9] studies showed that out of the four natural bases, guanine may form a π-stacking with the greatest chance of providing a conducting bridge between bases, due to its lowest oxidation potential. [9] Moreover, the robust quadruple helix, in which each tetrad (Figure 1a) is formed by eight hydrogen bonds rather than by two or three as in dsDNA, is more rigid than the duplex dsDNA helix and may withstand surface deformations in solid-state molecular devices.…”
mentioning
confidence: 99%
See 3 more Smart Citations